Efeito do gel a base de chá verde e ácido hialurônico sobre a cicatrização de sítios pós-extração de terceiros molares: estudo clínico, controlado e randomizado com modelo de boca dividida e duplo-cego. - Bonatto, Mariana da Silva (2022)
This study aimed to evaluate the effect of a gel based on green tea and hyaluronic acid on alveolar repair at sites after third molar extraction. For this, 22 participants who underwent extraction of the 4 third molars who were treated in a split-mouth model were included in this study. The oral mucosa of the surgical wound of the upper and lower molars on the test side was filled with green tea and hyaluronic acid gel, while the oral mucosa of the surgical wound of the upper and lower molars on the control side was filled with placebo gel. Soft tissue healing was evaluated through clinical analysis at 3, 7 and 14 days after the surgical procedure, where pain, swelling, healing and bleeding were evaluated, in addition to the presence of complications such as bone spicules and alveolitis. As result, the test side presented less secretion in inferior sites at seven days, less postoperative edema and a lower frequency of complications, compared to the control side. Thus, the use of green tea and hyaluronic acid-based gel can be beneficial in the postoperative clinical course of third molar extraction, and may be a safe and viable adjuvant treatment alternative to aid in soft tissue healing. A future, larger-scale study is needed to better assess the effects of the gel and consolidate its results and its clinical application.